News Shocks under Financial Frictions - Christoph Görtz; John Tsoukalas; Francesco Zanetti (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We examine the dynamic effects and empirical role of TFP news shocks in the context of frictions in financial markets. We document two new facts using VAR methods which provide robust evidence on the importance credit spreads for the propagation of news shocks. A DSGE model with financial frictions shows these are critical for the amplification of TFP news shocks. The very similar quantitative dynamics implied by VAR and DSGE methodologies provides support for the `news view' of business cycles.
Keywords: E2; E3; 330